Resistencias femeninas al franquismo. Para un estado de la cuestión - Di Febo, Giuliana (Cuadernos de Historia Contemporánea, 2006)
The paper concentrates on the analysis of (i) the main interpretative clues concerning women commitment in the struggle against Franco, and ii) the different types of interventions in “female” living spaces and places traditionally considered of a secondary or supportive nature. The reformulation of the concept of resistance and the corresponding revaluation of struggling modalities associated to solidarity, survival, dissidence or personal revolt, have made visible, in recent years, a complex and articulated women participation. Similarly, the study of the dictatorship repression types may offer significant research clues with respect to the “consensus” during Franco’s regime.